2010
DOI: 10.3141/2191-17
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide Benefits of Using Collection–Delivery Points for Failed Home Deliveries in the United Kingdom

Abstract: Unlike much of the previous research on this topic, which assesses the economic consequences of failed deliveries to the home, this study examines the issue of failed delivery from a carbon-auditing perspective. It considers the potential environmental savings from the use of alternative forms of collection and delivery over traditional delivery methods for failed home deliveries. With a spreadsheet carbon audit model, carbon dioxide (CO2) emissions for a failed delivery are calculated on the basis of a typica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 8 publications
2
82
1
2
Order By: Relevance
“…For instance, in a survey-based study, the author found that the e-commerce-related increase in freight transport was higher than the corresponding decrease in customer trips [9]. In general, the effects of e-commerce on transport are still uncertain and have been the focus of research during the last years [3,4,10]. Browne [11] argues that the traffic volume due to home deliveries is affected by several factors, such as the customer behaviour, the consolidation of deliveries and the number of returned goods.…”
Section: Urban Logistics and E-commerce Deliveriesmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in a survey-based study, the author found that the e-commerce-related increase in freight transport was higher than the corresponding decrease in customer trips [9]. In general, the effects of e-commerce on transport are still uncertain and have been the focus of research during the last years [3,4,10]. Browne [11] argues that the traffic volume due to home deliveries is affected by several factors, such as the customer behaviour, the consolidation of deliveries and the number of returned goods.…”
Section: Urban Logistics and E-commerce Deliveriesmentioning
confidence: 99%
“…Especially with the rise of e-commerce shopping, an increasing number of people order products online and have them delivered at home. Nowadays, this B2C distribution of parcels accounts for 56% of all shipments in e-commerce [1] and, thus, B2C e-commerce has been identified as a major challenge in the urban logistics literature [2][3][4][5][6]. The growth in parcel transportation is accompanied by an increase in externalities like emissions, which affect the quality of urban life in a negative way.…”
Section: Introductionmentioning
confidence: 99%
“…Studies by Song et al ) and Edwards et al (Edwards et al 2009;Edwards et al 2010) provide strong evidence to suggest that implementation of locker bank facilities at work locations would provide significant cost savings to carriers and customers in terms of reducing the travel associated with failed firsttime delivery attempts and the collection of items from couriers depots.…”
Section: Personal Deliveriesmentioning
confidence: 99%
“…Studies by Edwards et al (2009);Edwards et al (2010) and Song et al (2009) have demonstrated the significant savings in operating costs and carbon emissions can be achieved with unattended collection-delivery points in the context of home deliveries. Results from these studies indicated annual savings of between £2,778 ($4,123) and £6,459 ($9,585) in carrier's transportation costs and reductions in emissions of between 3.8 and 8.7 tonnes (4.18 to 8.59 tons) of CO2 as carbon ).…”
Section: Unattended Locker Box Conceptmentioning
confidence: 99%
See 1 more Smart Citation